Factors Affecting Labor Migration Abroad by Province in Indonesia - Puspitasari, Wahyu Indah; Kusreni, Sri (Jurnal Ilmu Ekonomi Terapan, 2017)
Labor migration abroad is one of the alternatives to solve unemployment. However, overseas migration does not just happen, many factors influence it. This study aimed to discuss the effects of unemployment, Gross Regional Domestic Product per capita, average years of education, and poverty on the labor migration to outside Indonesia by the province in Indonesia from 2010 to 2014. This study using Fixed Effect Model (FEM) analysis. The results of the analysis concluded that the variable number of unemployed, the GDP per capita, average years of education, and poverty simultaneous significant effect on labor migration out of Indonesia. Unemployment and poverty partially have significant effects on labor migration abroad. However, the average years of education and GDP per capita do not significantly affect labor migration.